Theoretical Management Enterprise Model in Global Market. Profitability and Rentability - Stefania Mariana VOICU (Annals of Dunarea de Jos University. Fascicle I : Economics and Applied Informatics, 2023)
Globalization influences and effects can be easily observed in all mediums and in all economic fields, meaning that significant measures, contributions and changes at all management levels has to made in order to ensure market competitiveness and profitability. Small and medium enterprises (SMEs) are facing significant obstacles after financial recessions, especially in assuring the financial support needed to fulfil the shareholders goals and objectives. The current state of challenges lead naturally to the development of different strategies in order to achieve the proposed development goals and therefore also those of shareholders and investors. In this study, we propose a dynamic competitive strategy for SMEs with the purpose of increasing the levels of competitiveness in a global and interconnected economic context. After discussing the proposed model and determining its theoretical effects, we strive to analyse the types of actions needed to ensure correct and efficient implementation of proposed strategy. Further discussions regarding prevention of negative effects induced by auxiliary costs are also presented in this conducted study. This paper also concerned itself with the conceptual issues of economic and financial competitive strategies and emphasizes as well the necessity for a theoretical model framework embracing financial decisions.